Knowledge, attitude and practice on the importance of green area among youths in Putrajaya - Fauzi, Ahmad Fudzail; Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2024)
Objective: This study investigated the relationship between knowledge, attitude and practice (KAP) on the importance of green area among youths in Putrajaya. Method: This was a cross-sectional study whereby, a (KAP) survey was conducted, involving community from 2 precincts in Putrajaya which are Presint 8 and Presint 9. A validated and pilot-tested questionnaire was distributed to 176 youths and results were analysed using SPSS. The questionnaire consists of four parts (social-demographic characteristic, general ques- tions, (KAP) on the importance of green area, recommendation). The data was analysed by descriptive frequency, Pearson correlation test and Mann-Whitney U test to find the association between KAP on the importance of green area among youths in Putrajaya. Result: This study found a significant relationship between knowledge towards importance of green areas of Presint 8 and Presint 9 by using Mann-Whitney U test for independence. However, there was no association between attitude and practice on the importance of green area. The findings further showed there is a moderate level of knowledge, attitude and practice towards the importance of green areas. The study discovered that social media is the primary source for information regarding the importance of green areas for them. Conclusion: This study indicates that the respondents have moderate level of knowledge, attitude and practice towards the importance of green areas. The finding of data from youths in Putrajaya KAP data can be used as a reference to formulate effective health promotion intervention to increase the use of green spaces that would have a good impact on society, as wellas on the economy and the environment of the country.